2001
DOI: 10.4049/jimmunol.166.10.6074
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ Tumor-Infiltrating Lymphocytes Are Primed for Fas-Mediated Activation-Induced Cell Death But Are Not Apoptotic In Situ

Abstract: Induction of Fas-mediated activation-induced cell death in antitumor T cells has been hypothesized to permit tumor escape from immune destruction. Several laboratories have proposed that expression of Fas ligand (L) by tumor is the basis for this form of T cell tolerance. In this study, we characterized murine tumor-infiltrating lymphocytes (TIL) for activation status, cell cycle status, level of apoptosis, cytokine secretion, and proliferative capacity. TILs express multiple activation markers (circa CD69, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 37 publications
(31 reference statements)
7
73
0
Order By: Relevance
“…23 and 24). Some authors have reported increased apoptosis of tumorinfiltrating lymphocytes (25), although contrary findings have also been shown (26). We hypothesized that myeloid cells localized in tumor tissues, and ones localized in peripheral lymphoid organs (spleen) may differ in their ability to suppress T cell responses.…”
Section: Stat1 Signaling Regulates Tumor-associated Macrophage-mediatmentioning
confidence: 79%
“…23 and 24). Some authors have reported increased apoptosis of tumorinfiltrating lymphocytes (25), although contrary findings have also been shown (26). We hypothesized that myeloid cells localized in tumor tissues, and ones localized in peripheral lymphoid organs (spleen) may differ in their ability to suppress T cell responses.…”
Section: Stat1 Signaling Regulates Tumor-associated Macrophage-mediatmentioning
confidence: 79%
“…Tumor-specific CD8 T cells lacking effector activity have been isolated from progressing tumors (11)(12)(13), as well as tumor-infiltrated LN of melanoma patients (17,18). In most of these reports, the basis for dysfunction was not established, although the ability to detect these cells in significant numbers suggests that they were able to proliferate in response to Ag at some point.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, such dysfunctional CD8 T cells have been isolated from tumors (11)(12)(13). If such T cells are rested in vitro, they recover effector function (11,12), suggesting that factors in the tumor microenvironment suppress the effector activity of otherwise fully differentiated T cells. Several tumors or cells infiltrating tumor masses secrete immunosuppressive cytokines such as TGF-␤ and IL- 10 (14, 15), and these factors may induce local suppression of CD8 T cells.…”
Section: Incomplete Differentiation Of Antigen-specific Cd8 T Cells Inmentioning
confidence: 99%
“…This mechanism involves the overexpression of both Fas and FasL upon activation by antigen or other stimuli, subsequently pro oti g ell suicide or fratricide [3]. Decreased Fas and elevated FasL expression has been found in many types of cancer including bladder cancer [4].…”
Section: Introductionmentioning
confidence: 99%